Formacja nowych ewangelizatorów dla dzieła nowej ewangelizacji - Izabela Iwańska (Polonia Sacra)
The new evangelization needs new evangelizers. Every Christian is called to bear witness to faith, his deeds and words. No one is born evangelizer, but a person becomes evangelizer in the way of the formation. To form the new evangelizer for the new evangelization, you must clearly define the vision and the purpose to which we are going toward. We want to form him according to the assumptions of the new evangelization. The new evangelization is new in the enthusiasm, new in the method and new in the means of expression. The formation of the new evangelizers for the new evangelization, is an integral formation, involves the whole person and takes place continuously, day after day. The formation method was taken from the Bible. It consists of the formation of the disciples. It is important to choose people who will be able to form the next disciples. The formator, the trainer or the teacher is needed in the process of formation. This may be the person who have gone thought this way, and he goes on it further, keeping in mind that Christian always teaches to evangelize by evangelizing.